The Mediating Effect of Nurses’ Emotional Intelligence in the Relationship between Moral Sensitivity and Communication Ability with Angry Patients - Guo, Si-Yan; Wang, Xiao-Kai; Zhang, Zhen-Xiang; Zhang, Qiu-Jun; Pan, Xue; Li, Cai-Xia; Ke, Dan-Dan (Journal of nursing management, 2024)
Aims . To test whether emotional intelligence plays a mediating role in the process by which moral sensitivity affects nurses’ ability to communicate with angry patients. Background . Hospital workplace violence is a global problem that disrupts the normal work order of healthcare, undermines trust between nurses and patients, and threatens the physical and mental health of nurses. Improving nurses’ ability to communicate with angry patients to identify and diffuse patients’ anger is critical to reducing the nurse‐patient conflict and avoiding violence in the hospital workplace. Methods . The data were collected in China. A sample of 212 nurses completed measures of moral sensitivity, emotional intelligence, and the ability to communicate with angry patients. Structural equation modeling was used to test the study’ hypothesis. Results . Our results suggest that nurses’ emotional intelligence mediates the relationship between nurses’ moral sensitivity and nurses’ ability to communicate with angry patients, with a positive correlation between nurses’ moral sensitivity, emotional intelligence, and ability to communicate with angry patients. Conclusions . The findings showed that nurses’ moral sensitivity indirectly influenced nurses’ ability to communicate with angry patients by directly influencing emotional intelligence. This study provides a theoretical and methodological approach to mitigate nurse‐patient conflict and reduce violence in the hospital workplace through a moral perspective. Implications for Nursing Management . Nursing managers should pay attention to the moral sensitivity and emotional intelligence of nurses and promote their moral development and emotional intelligence by strengthening moral education in hospitals, utilizing emotional intelligence training courses and narrative nursing, ultimately promoting nurses’ ability to communicate with angry patients, further contributing to the reduction of nurse‐patient conflict, avoiding violence in the hospital workplace, building a safer hospital environment, promoting the overall development of nurses, and contributing to the development of global health and wellness.